Chromium(VI) Ion Removal from Aqueous Solutions Using a Zn–Al-Type Layered Double Hydroxide - Laura Cocheci; Paul Barvinschi; Rodica Pode; Elena-Mihaela Seftel; Eveline Popovici (Adsorption Science & Technology, 2010)
This paper deals with the structural and adsorptive characterisation of a Zn–Al-type layered double hydroxide to be used for the retention of chromate ions from aqueous media. Structural characterisation by X-ray diffraction and FT-IR spectroscopy showed that the material was a layered double hydroxide with carbonate in the interlayer; however, certain impurities were also identified. Thermogravimetric analysis allowed appropriate calcination temperatures to be chosen for the sorption studies. The equilibrium adsorption of the Cr(VI) ion was best described by the Langmuir–Freundlich equation. Calcining the material at 500 °C led to a product containing mostly stable zinc oxide with low adsorptive properties. The kinetics of Cr(VI) ion retention on the uncalcined layered double hydroxide obeyed the pseudo-first-order model as described by the Lagergren equation. Structural analysis of the product obtained after Cr(VI) ion sorption onto Zn–Al–CO 3 showed that the carbonate anion was not replaced in the interlayer and that the Cr(VI) ion was adsorbed within cavities formed by three adjacent metal hydroxide octahedra situated at the edge of the brucite-like layer.